Community Satisfaction Index on Public Service Performance of UPTDLabkesda Samarinda - Eko Prasetya Budi; Ratno Adrianto; Ike Anggraeni Gunawan (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Public service satisfaction surveys are an essential instrument for evaluating the quality and performance of government institutions in delivering public services. The Regional Health Laboratory Unit (UPTD Labkesda) of Samarinda City periodically conducts Community Satisfaction Surveys (CSS) to assess public perceptions, identify strengths and weaknesses in service delivery, and ensure compliance with the service quality standards established under Ministerial Regulation of PANRB No. 14 of 2017 on Guidelines for Conducting Community Satisfaction Surveys. Objective : The study aims to measure the level of community satisfaction with the services provided by UPTD Labkesda Samarinda during the first semester of 2025 and to identify service elements that require improvement to enhance the overall quality and efficiency of public health laboratory services. Research Methods/ Implementation Methods : A descriptive quantitative approach was employed using a structured survey method. Respondents rated nine service elements using a four-point Likert scale, and the results were processed to obtain the Community Satisfaction Index (CSI) Results : The survey results show that the Community Satisfaction Index reached 87.28, categorized as “Satisfactory.” This indicates that most respondents perceive the services as effective, professional, and aligned with their expectations. Conclusion/Lesson Learned : The findings reveal that UPTD Labkesda Samarinda has successfully maintained a high level of public satisfaction through consistent service quality, competent staff, and adequate facilities. Continuous efforts in staff development, process optimization, and community feedback mechanisms are essential to sustain and further improve service outcomes.